Association Between Active or Passive Smoking and Allergic Rhinitis: an Evidence-Based Case Report: Smoking and Allergic Rhinitis - Lupita Reksodiputro; Thalia Mufida; Niken Poerbonegoro; Mirta Hediyati Reksodiputro (Faculty of Medicine Universitas Indonesia, 2021)
This evidence-based case report (EBCR) aims to investigate the association between active or passive smoking with allergic rhinitis by summarizing existing studies on the topic. A literature search was done on major databases with keywords related to this study’s research question. The literature was appraised using CEBM University of Oxford for etiology study and systematic review sheets. The search obtained two articles for critical appraisal, includes a meta-analysis and a cohort study. The studies were appraised as valid, important, and applicable to the writer’s setting. Saulyte et al’ s2 article described RR active smoking with allergic rhinitis of 1.02 (95%CI 0.92-1.15), with no significant association. They resolved the heterogeneity by making subgroups. The cross-sectional subgroup with RR 1.09 (95%CI 1.06-1.12) is statistically significant. There was a significant association in passive smoking and obtained RR 1.10 (95%CI 1.06-1.15). In the study by Mlinaric et al4 the RR of active and passive smoking compared to non-smoker are 1.82 and 2.00; both show statistical significance. Both active and passive smoking is associated with a high risk of allergic rhinitis in adults and children. Keywords active smoking, passive smoking, allergic rhinitis. Hubungan Perokok Aktif dan Pasif dengan Rhinitis Alergi: Laporan Kasus Berbasis Bukti Abstrak Pada laporan kasus berbasis bukti ini bertujuan untuk menginvestigasi hubungan antara perokok aktif dan perokok pasif pada pasien dengan rinitis alergi. Dilakukan pencarian literatur menggunakan kata kunci yang berhubungan dengan kasus pada beberapa search engine, kemudian dilakukan penilaian kelayakan dengan lembar appraisal dari CEBM University of Oxford for etiology study and systematic review sheet. Dari pencarian didapatkan dua artikel yang mepresentasikan kasus tersebut, yaitu studi meta analisis dan studi cohort. Studi meta analisis oleh Saulyte et al2 menyatakan RR pada perokok aktif dengan rinitis alergi adalah 1,02 (95%CI 0,92-1,15). Pada subgrup potong lintang didapatkan perbedaan bermakna dengan RR 1,09 (95%CI 1,06-1,12). Pada studi cohort oleh Minaric et al didapatkan RR pada perokok aktif 1,82 dan pada perokok pasif 2,00, keduanya menunjukan angka yang signifikan. Pada perokok aktif dan pasif berhubungan dengan risiko tinggi pada rinitis alergi di pasien dewasa dan anak-anak. Kata kunci: perokok aktif, perokok pasif, rhinitis alergi.